Mobilité et archéologie le long de l’arc oriental du Niger : pavements et percuteurs - Anne Haour (Afriques)
This analysis of the role of migration in West Africa begins by recalling the prevalence of oral traditions about so-called 'first-comers', and takes the example of dry season migrations in the Hausa area (cin rani). To what extent do such ideas worked out in relation to contemporary events help us interpret archeological findings, in particular by taking into account the idea of the “space of experience” that tries to reconstitute the social context of human activities? Two sorts of technical behavior are examined here: the making of pottery by pounding on a concave mould and the use of a pavement of ceramic shards. The preliminary findings of archeological excavations in northern Bénin are taken as a case study; and the suggestion is made that the use of these two techniques can be used as evidence of migrations.